Diversity of flora and fauna in various forest ecosystem types of South Sorong District, Southwest Papua Province, Indonesia - OBED N. LENSE; JIMMY F. WANMA; FRANCINA F. KESAULIJA; FADHILAH I. MANSYUR; ARMANSYAH K. RACHIM; KELIOPAS KREY; BEATRIX WANMA; REYNOLD KESAULIJA; DINOSIUS SIMANJORANG; FIKTOR SIMBIAK (Society for Indonesian Biodiversity, 2024)
Abstract. Lense ON, Wanma JF, Kesaulija FF, Mansyur FI, Rachim AK, Krey K, Wanma B, Kesaulija R, Simanjorang D, Simbiak F. 2024. Diversity of flora and fauna in various forest ecosystem types of South Sorong District, Southwest Papua Province, Indonesia. Biodiversitas 25: 3884-3898. The distribution of unspoiled natural conditions, uniqueness, and high biodiversity are not limited to conservation areas but also to production and protected forest areas and other land use areas in Southwest Papua Province, Indonesia. These forest ecosystems have high flora, fauna, and areas that are priority animal pockets whose home ranges reach and enter essential ecosystem areas. However, the need for such diverse information has been an issue in this region. Hence, a diversity study of vegetation, mammals, birds, reptiles, amphibians, and butterflies in various ecosystem types is needed. The six types of ecosystems, namely the alluvial lowland forest of Nakna, the lowland karst forest of Boldon, the lowland limestone forest of Wara, the alluvial swamp forest of Konda, the peat swamp forest of Nakna, and the mangrove forest of Konda, were targeted. The line-plotted method was used for vegetation. Direct observation on a 1,500 m line transect, the point count method, and the Visual Encounter Survey were employed to collect data from mammals, birds, reptiles, amphibians, and butterflies. Results indicated that the lowland limestone forest of Nakna and the lowland karst forest of Boldon consisted of the highest number of trees (532 and 373 trees ha-1, respectively), species (56 and 52 species ha-1, respectively) per unit area. Unique and endemic orchid species, including Dendrobium transversilobum J.J.Sm. and Bulbophyllum septemtrionale (J.J.Sm.) J.J.Sm., also exist in this region, adding to the wonder of the region's biodiversity. The research also discovered a total of 9 species of mammals, 52 species from 25 families of birds, 39 species of reptiles and amphibians, of which species Litoria sanguinolenta (Van Kampen, 1909) is a new record to the region and 58 species of day butterflies from the Papilonoidea superfamily. Several key species of flora and fauna in this region require special attention as they are in alert status, which may require intervention to maintain their existence in nature so that they do not disappear or even become extinct.